Perspektif H.O.S Tjokroaminoto Tentang Pendidikan, Islam, dan Nasionalisme - Farijal, Farijal; Gufron, Iffan Ahmad; Masykur, Masykur (Permata : Jurnal Pendidikan Agama Islam, 2023)
The journey of human life will not be separated from various things that require the use of reason to be able to determine the outcome of every problem faced. The paradigm of thinking is influenced by the concentration of education pursued, so the important role of education will be comparable to the output of processing reason on a problem that uses thinking as its basic tool. However, there is something more important than education, namely Religion, because religion is a foundation of life. Which cannot be accepted only by reason, but by faith. Tjokroaminoto as one of the revolutionary educational figures in Indonesia who is determined to carry out every movement on a religious basis, resulting in extraordinary student products such as Soekarno, Kartosuwiryo and Semau'n. This research will examine Islam as a revolutionary education from the perspective of H.O.S Tjokroaminoto.Keyword: Islam; Education; Tjokroaminoto.